Development of emergency nursing care competency scale for school nurses - Jaehee Yoon (BMC, 2021)
Abstract Background School nurses perform vital student emergency services at school, and assessing their emergency nursing care competency is critical to the safety and quality of care students receive. The purpose of the study was to develop a scale for measuring school nurses' competency. Methods This was an instrument development and validation study. It was conducted according to the revised DeVellis scale development process coupled with the application of the International Council of Nurses' Nursing Care Continuum Competencies Framework. Eight experts specializing in school health and emergency care evaluated the content validity, while 386 school nurses evaluated the scale. The validity evaluation comprised factor analysis, discriminative validity analysis according to differences in school nurse experience, and criterion validity analysis. Scale internal consistency was analyzed using Cronbach's α value. Results The final scale comprises a self-reported 5-point Likert scale with 30 items based on three factors and three sub-factors. Both the convergent validity of the items by factor and the discriminative validity were both confirmed. The criterion validity was also found to be positively correlated with the Triage Competency Scale. Conclusion The scale may be used to identify factors influencing school nurses' competency in emergency nursing care and contribute to research in competency-based education programs.